Formalization of the Domination Chain with Weighted Parameters - Severín, Daniel Esteban (2019)
The Cockayne-Hedetniemi Domination Chain is a chain of inequalities between classic parameters of graph theory: for a given graph G, ir(G) ≤ γ(G) ≤ ι(G) ≤ α(G) ≤ Γ(G) ≤ IR(G). These parameters return the maximum/minimum cardinality of a set satisfying some property. However, they can be generalized for graphs with weighted vertices where the objective is to maximize/minimize the sum of weights of a set satisfying the same property, and the domination chain still holds for them. In this work, the definition of these parameters as well as the chain is formalized in Coq/Ssreflect.